2014
DOI: 10.1111/poms.12043
|View full text |Cite
|
Sign up to set email alerts
|

First Step in Social Media: Measuring the Influence of Online Management Responses on Customer Satisfaction

Abstract: With the growing influence of online social media, firms increasingly take an active role in interacting with consumers in social media. For many firms, their first step in online social media is management responses, where the management responds to customers' comments about the firm or its products and services. In this article, we measure the impact of management responses on customer satisfaction using data retrieved from a major online travel agency in China. Applying a panel data model that controls for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
220
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(237 citation statements)
references
References 49 publications
(96 reference statements)
5
220
0
1
Order By: Relevance
“…Instead, the service provider's response to the failure or lack of response is the most likely cause of dissatisfaction (Smith et al, 1999). Gu and Ye (2013) studied the impact of management responses on customer satisfaction using data retrieved from a major online travel agency in China. They found that online management responses are highly effective among low satisfaction customers but have limited influence on other customers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Instead, the service provider's response to the failure or lack of response is the most likely cause of dissatisfaction (Smith et al, 1999). Gu and Ye (2013) studied the impact of management responses on customer satisfaction using data retrieved from a major online travel agency in China. They found that online management responses are highly effective among low satisfaction customers but have limited influence on other customers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, McCollough and Bharadwaj (1992) have found that satisfaction of users who have come across service failures and then have received solutions after service failure is as high as or even higher than satisfaction of those who haven't experience any failure. Similarly, Gu and Ye's (2012) study shows that provider's effective responses improve users' satisfaction for those with low satisfaction level. Furthermore; Krishen et al (2015) have conducted a study among Facebook, Twitter, LinkedIn and other social media firm users.…”
Section: Effects Of User Satisfactionmentioning
confidence: 99%
“…Appendix Table A3) In the area of services management, the main topics that have been empirically examined are (a) the causal relationship between customer satisfaction and various operational metrics and (b) the effects of introducing self-service technology and e-services. Two notable empirical studies on the first topic are by Lapré (2011) and Gu and Ye (2014). The notable papers on the second topic include those by Tsikriktsis et al (2004), Xue et al (2007), Buell et al (2010), and Campbell and Frei (2010).…”
Section: Quality Management (Onlinementioning
confidence: 99%